El léxico eslovaco y su evolución: panorámica general (1). - Alvarado, Salustio (Eslavística Complutense, 2002)
Although its basis is fiindamentally Slavonic, the Slovak vocabulary consists, to a greater or lesser degree, of elements of different origins. This article presents some general ideas about its incorporation into the language. The problem ofbohemianisms is particularly thorny. Since etymological studies of Slovak are not very abundant, especially conceming Eastern languages, and considering no etymological dictionary of Slovak has so far been published, this essay, initialLy devised for students who have optionally chosen "History of the Slovak Language", can be a modest contribution in this field. Dueto the Iength ofthis article, it will be published in two parts.